Understanding the Domain of Cross-National Buyer-Seller Interactions - Kale, Sudhir H.; Barnes, John W. (Journal of International Business Studies, 1992)
Cross-national face-to-face selling has thus far received very little scholarly treatment in marketing literature. With few notable exceptions, most existing research in this area has been fragmentary and opportunistic. These problems are largely because of the lack of a broad, generalizable framework within which to conceptualize and execute research studies. In offering such a conceptual framework, this article looks at buyer-seller interactions from a communication perspective.